Bio-inspired self-assembly of large area 3D Ag@SiO2 plasmonic nanostructures with tunable broadband light harvesting. (December 2021) - Cheng, Pengfei; Ziegler, Mario; Ripka, Valentin; Wang, Dong; Wang, Hongguang; van Aken, Peter A.; Schaaf, Peter
Highlights: Inspired by the coral tentacle, super large-scale (153 cm 2 ) 3D Ag@SiO2 hybrid plasmonic nanostructures with adjustable and ultra-broadband light absorption are fabricated by a metastable atomic layer deposition (MS-ALD) combined with physical vapor deposition (PVD) approach. 3D Ag@SiO2 hybrid plasmonic nanostructures are generated in a controllable self-assembly manner. Finite-difference time-domain (FDTD) simulation demonstrates that the excellent light absorption properties are attributed to multiple forward scatterings and extinction effects produced by Ag@SiO2 nanostructures. Using 3D Ag@SiO2 plasmonic nanostructures as light absorber for solar water evaporation, the water evaporation rate remarkably improves seven times under 1 sun than that in dark condition. Abstract: Tremendous efforts have been made to fabricate large-scale plasmonic nanostructures, which show wide applications in surface plasmon resonance (SPR) sensing, catalytic conversion, photothermal conversion, optoelectronics, photothermal therapy. However, unable to fabricate over 5 cm 2 plasmonic nanostructures with good controllability hinders their further applications. Here, super large-scale (153 cm 2 ) 3D Ag@SiO2 hybrid plasmonic nanostructures with adjustable and ultra-broadband light absorption are fabricated by a simple and controllable two-step approach. The metastable atomic layer deposition (MS-ALD) is combined with physical vapor deposition (PVD) to generate these structures in a self-assembly manner. The structures look like coral tentacles. These excellent properties are attributed to multiple forward scatterings and extinction effects produced by Ag@SiO2 nanostructures. Using 3D Ag@SiO2 plasmonic nanostructures as light absorber for bottom-heating-based evaporation, the water evaporation rate remarkably improves seven times under 1 Sun than that in dark condition. Our results pave the avenue for developing super large-scale Ag-based plasmonic nanostructure with potential applications in solar energy conversion. Graphical abstract: Bio-inspired large-scale 3D Ag@SiO2 plasmonic nanostructures with tunable broadband light harvesting are fabricated by metastable atomic layer deposition combined with physical vapor deposition in a self-assembly manner. Image, graphical abstract